Prevention of maternal and neonatal complications - Faneite Antique, Pedro (2015)
Etiopathology in Perinatal Medicine. Reflections. How to eliminate medical errors in obstetrics. Preventability of adverse events in patients hospitalizadas.Plan prenatal care in multiple pregnancy. Nutrition: How to get a newborn quality. Forecast timely management of neonatal resuscitation. Detection and diagnosis of gestational diabetes. Prevensión of preeclampsia. Preventing preterm birth. The genome for predicting preterm delivery. Controversies in the management of preterm labor.